Produksi dan Mutu Tomat (Lycopersicum esculentum Mill.) Akibat Pemupukan Kimia, Organik, Mineral, dan Kombinasinya pada Inceptisol Kebun Percobaan Fakultas Pertanian Universitas Udayana - ARIHTA FEBRINA SIANTURI; NENGAH NETERA SUBADIYASA; DEWA MADE ARTHAGAMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Production and Quality of Tomatoes (Lycopersicum esculentum Mill.) Due to Chemical, Organic, Mineral Fertilization, and The Combination of Fertilizer in Inceptisol Experimental Garden Agriculture Faculty of Udayana University The purpose of this research is to know the influence of some fertilizers to increase production and quality of tomatoes at Inceptisol, as well as chemical properties at Pegok. This research was held on August until November 2016 at the Experimental Garden, Faculty of Agriculture, and the Laboratory of Soil and Environmental Sciences Faculty of Agriculture, University of Udayana. The design used was a Randomized Block Design (RBD) with seven fertilization treatments and three replication with the number of plots 21 consist of P0 = Control, P1 = Organic fertilizers, P2 = Mineral fertilizers, P3 = Chemical fertilizers, P4 = fertilizer combination (PO + PK), P5 = fertilizer combination (PM + PK), P6 = fertilizer combination (PO + PM + PK). Statistical test by analysis of variance was significantly different when followed by LSD (Least Significance Different) test with a confidence level of 95% using Costat program.The role of chemical fertilizers are increase tomatoes production, the highest 54,67 tonnes ha-1 in treatment P3 (200 kg Phonska and 200 kg Urea) ha-1 up 207,12% compared with P0 (Control) is 17,80 tonnes ha-1, followed by P6 (5 tonnes Organic Fertilizer + 2,5 tonnes Chemical Fertilizer + 100 kg Phonska + 100 kg Urea) ha-1 is 41,20 tonnes ha-1 up 131,46% compared with P0 (Control), P5 (100 kg Phonska + 100 kg Urea + 2,5 tonnes Chemical Fertilizer) ha-1 is 40,13 tonnes ha-1 up 125,47% compared with P0 (Control), P4 (5 tonnes Organic Fertilizer + 2,5 tonnes Chemical Fertilizer) ha-1 is 28,53 tonnes ha-1 up 60,30% compared with P0 (Control), P1 (10 tonnes Organic Fertilizer) ha-1 is 27,60 tonnes ha-1 up 55,06% compared with P0 (Control), P2 (5 tonnes Chemical Fertilizer) ha-1 is 26,33 tonnes ha-1 up 47,94% compared with P0 (Control). The highest quality of tomato was shown by formula of P5 : combination of chemical and mineral fertilizer.